Spermatozoa quality and sperm lipid composition in intensively cultured and wild burbot (Lota lota) - Blecha, Miroslav; Dzyuba, Boris; Boryshpolets, Sergii; Horokhovatskyi, Yevhen; Dadras, Hadiseh; Malinovskyi, Oleksandr; Sampels, Sabine; Policar, Tomáš (Animal reproduction science, 2018)
The aim of this study was to compare the spermatozoa quality parameters in spermatozoa of RAS (Recirculating Aquaculture System; RAS group) cultured (commercial pellets) and natural condition cultured (WILD group) burbot Lota lota (live prey, Pseudorasbora parva). Seven of nine fish of the RAS group produced sperm, with sperm from only four of the fish having a motility of >5%. Sperm were collected from all nine fish of the WILD group, and sperm of six of the fish from the WILD group had motility of about 100% and three had sperm with 50% to 60% motility. Spermatozoa from the RAS group had a delay in activation compared to the WILD group. Fish from the RAS group also had a lesser volume of sperm (1.8 ± 1.2 mL) collected compared to the WILD group (3.6 ± 1.2 mL). Compared to the RAS group, sperm of the WILD group had a greater proportion of saturated fatty acids (SFA), as well as the phospholipid, phosphatidylethanolamine. The findings indicate that fish grown in natural conditions may be more suitable as broodstock. Ongoing research to develop methods of enhancing reproductive performance of burbot broodstock cultured in RAS is needed to investigate whether the quality of sperm can be improved by adjusting environmental conditions, diet, or combination of these factors.
Keywords: divoká zvířata; analýza spermatu; zvířata; Spermatozoa; mastné kyseliny; CASA; Gadiformes; Aquaculture; Fatty Acids; Lipids; mužské pohlaví; WOB; vodní hospodářství; Milt; VCL; Reproduction; Animals, Wild; Animals; metabolismus lipidů; Semen Analysis; Lipid Metabolism; spermie; Male; lipidy